STRUKTUR KEPEMILIKAN DAN KINERJA PERBANKAN - Sparta; Sarah Hani Mahdiyah (Ibs Press, 2025)
This study focuses on research of relationship between ownership structure and banking performance and to know if GCG as moderation variable can strengthen their relationship. This study is using panel data covering 5 years from 32 banking firms listed in Bursa Efek Indonesia. The result shows that managerial ownership and institutional ownership are significant determinants of banking performance. However, this study do not find a significant relationship between government ownership and banking performance. Other than that, GCG as moderation variable can strengthen the relationship between managerial ownership and institutional ownership to banking performance but cannot strengthen the relationship between government ownership and banking performance.